2009
DOI: 10.4319/lo.2009.54.3.0890
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of point‐source groundwater discharges to the ocean from the shoreline of the Big Island, Hawaii

Abstract: Aerial thermal infrared imaging has revealed that submarine groundwater discharge (SGD) along the western coast of the Big Island of Hawaii is often focused as point-source discharges that create buoyant groundwater plumes that mix into the coastal ocean. We quantified the SGD fluxes associated with several plumes using natural geochemical tracers. Offshore transects of 222 Rn and 224 Ra show elevated activities and corresponding low salinities in the nearshore waters within the plumes, indicating that these n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(90 citation statements)
references
References 25 publications
7
79
4
Order By: Relevance
“…Submarine groundwater discharges into the coastal ocean can be significant in Hawai'i (Peterson et al 2009), but we do not know the magnitude of this process in our study area. (Hoover et al 2006).…”
Section: Re Sults the Storms And Their Effectsmentioning
confidence: 80%
“…Submarine groundwater discharges into the coastal ocean can be significant in Hawai'i (Peterson et al 2009), but we do not know the magnitude of this process in our study area. (Hoover et al 2006).…”
Section: Re Sults the Storms And Their Effectsmentioning
confidence: 80%
“…SGD fluxes from the Hawaiian Islands are poorly quantified, having been modeled in a few discrete locations only (Johnson et al, 2008;Knee et al, 2008;Street et al, 2008;Peterson et al, 2009), but none of these efforts have targeted the total SGD flux from an entire island or the archipelago as a whole. The USGS has performed whole-island water budget studies for all the major Hawaiian Islands except for the island of Hawai'i, where the water budget has been described in several regional studies (performed by the USGS, the State of Hawai'i and private companies), which together cover the entire island.…”
Section: Hydrologymentioning
confidence: 99%
“…For example, SGD from the island of Hawai'i has a temperature of ~19-21°C (Johnson et al, 2008;Peterson et al, 2009), andConrad et al (1997) showed that groundwater in deep drill holes on the east flank of Kilauea volcano is the same temperature from sea level down to ~500 m below sea level -~20-25°C. The results from Rad et al (2007) are therefore not directly comparable with our work.…”
Section: Water Chemistry and Chemical Fluxesmentioning
confidence: 99%
See 2 more Smart Citations